2013
DOI: 10.1111/jonm.12092
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of exemplary nurse leaders: perspectives of frontline nurses

Abstract: The findings are of significance to leaders in the health care system and in the nursing profession who are in a position to foster development of leaders to mentor and encourage frontline nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 21 publications
4
38
0
1
Order By: Relevance
“…Our findings also show that NMs who use different knowhow in nursing management, based on evidence or best practices, bring a sense of motivation and achievement to the workplace. [65][66][67][68][69][70] In this regard, our results are in line with those reported by Mackoff, Glassman, and Budin [66] in their qualitative participatory action study with 43 NMs that examined the development of a learning laboratory based on knowledge and experiences. Their results indicated that a learning culture within the healthcare organization offered learning activities addressing the needs of NMs.…”
Section: 4supporting
confidence: 82%
See 3 more Smart Citations
“…Our findings also show that NMs who use different knowhow in nursing management, based on evidence or best practices, bring a sense of motivation and achievement to the workplace. [65][66][67][68][69][70] In this regard, our results are in line with those reported by Mackoff, Glassman, and Budin [66] in their qualitative participatory action study with 43 NMs that examined the development of a learning laboratory based on knowledge and experiences. Their results indicated that a learning culture within the healthcare organization offered learning activities addressing the needs of NMs.…”
Section: 4supporting
confidence: 82%
“…These activities remain a prerequisite for role transition and enhance novice's attraction and retention. This is confirmed, also, by Anonson et al [70] in their works on transformational mentoring. According to Kelly, Wricker and Gerkins, [71] Mayrand Leclerc, [72] Shiparski and Authier, [73] mentorship programs would better prepare NMs and give them the required boost to meet economic and humanistic requirements and learn to use new technologies.…”
Section: Personalized Support Addressing the Specific Needs Of Novicesupporting
confidence: 77%
See 2 more Smart Citations
“…The values and practices of supportive leaders seem to be widely appreciated within nursing communities, with the personal morality and reflective behaviour of senior figures linked to constructive employee relations (Cleary et al, 2011;Eneh and Vehvilainen-Julkunen, 2012;Anonson et al, 2014;Wing et al, 2015). Endorsements were usually qualified, however, with nurses magnifying the limits placed on their own autonomy and the difficulties confronting leaders who try to sustain a permissive approach (Haycock-Stuart and Kean, 2013).…”
Section: Stakeholder Interpretationsmentioning
confidence: 99%